Relating the curriculum to regional concerns: a Japanese case study 1 - Gregory, Hadley (Penerbit UKM, 2003)
Globalisation, regionalisation, calls for various approaches to the teaching of English as an International Language (EIL) , a s well as pragmatic and critical pedagog ic considerations have stimulated d ebate in Japan about the focus of its English language curricula. This interdisciplinary case study weaves together the threads of different dynamics to create a framework for understanding the development of EIL curricul a in Japanese universities. The work underway in the Communicative English Programme (CEP) at Niigata University of International and Information Studies (NUIS) will be highlighted as one example of what is currently taking place in some corners of Japanese EIL .